Resistin in mid-trimester amniotic fluid in trisomy 21. (November 2013) - Vrachnis, N.; Gkogkas, L.; Iliodromiti, S.; Grigoriadis, C.; Samoli, E.; Iliodromiti, Z.; Pangalos, C.; Pappa, K.I.; Drakoulis, N.; Creatsas, G.; Botsis, D.
Abstract Objective: The aim of this study was to examine whether resistin is present in second trimester amniotic fluid from trisomy 21 (also known as Down's syndrome) pregnancies and whether its concentration differs compared with euploid pregnancies. Methods: The study cohort consisted of 58 women in the mid-trimester of pregnancy who underwent amniocentesis for prenatal diagnosis, 31 of whom carried a single fetus with diagnosed trisomy 21 (study group) and the rest with normal karyotype (control group, n = 27). Groups were matched for maternal and gestational age. Levels of resistin in amniotic fluid were measured by a commercially available enzyme-linked immunosorbent assay (ELISA) kit. Results: Resistin was detected in all amniotic fluid samples. Its median concentration in the second trimester amniotic fluid of trisomy 21 pregnancies (2.1 ng/ml) was statistically significantly lower (p value <0.001) in comparison with that in euploid pregnancies (3.3 ng/ml). Conclusions: Resistin is a physiologic constituent of second trimester amniotic fluid. Lower levels of amniotic fluid resistin in pregnancies with trisomy 21 may reflect altered metabolic pathways in utero that could possibly be related with phenotypic features of the syndrome.